Narrative Discourse of Painting “The Barque of Dante” 1822 in the Scene of the Movie “The House That Jack Built” 2018 - Huda, M A; Hidayatullah, T (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2022)
The purpose of this study is to learn how director Lars Von Trier implemented metatextuality discourse from a visual narrative text, the painting The Barque of Dante (1822) by Eugène Delacroix, for a scene of the film The House That Jack Built (2018). The film offers a visual narrative text similar to the painting whose represents a verbal narrative text, the epic poem Divine Comedy by Dante Alighieri. Qualitative research methods and Gerard Genette’s narrative discourse analysis will be used in this study. Hence it would be found how the metatextuality occurs from the visual narrative text of the painting to the film scene. The technique to collect data using literature study and observation, for critically explore and observe the research object. The study result could demonstrate how a visual narrative, the painting, is present in another visual narrative in the form of a metatextuality film scene. After the metatextuality implemented by Lars Von Trier, it helps to construct the visual narratives of his film scene so the main story and message could be delivered well to the audience. This research is capable of having an impact on the development of cinema’s visual narrative power by providing metatextuality in it.